Perpustakaan dan Manifestasi Belajar - Supardi Supardi (Institut Agama Islam Negeri Salatiga, 2019)
Education is basically a conscious effort to develop the potential of human resources by encouraging and facilitating learning activities. Self-learning activities are actually natural human processes in their lives. By learning humans get a lot of benefits, the most important thing is how to realize learning goals in order to maintain survival. In this paper described the importance of learning, the variety of learning and manifestations or manifestations of learning and the role of libraries in the realization of learning